Extraction of Natural Colorant from Clitoria ternatea Flowers Using Conventional Solvent Extraction (CSE) and Ultrasound-Assisted Extraction (UAE) Techniques: Kinetic Modeling and Compound Stability - Pra Cipta Buana Wahyu Mustika; Hadiyatni Rita Priyantini; Eryan Dwi Krisna; Firman Aldani; Fikrah Dian Indrawati Sawali; Moh Azhar Afandy; Mega Mustikaningrum (Jurnal Kimia Sains dan Aplikasi, 2024)
The Clitoria ternatea flowers, a prevalent local commodity in Indonesia, are extensively found, particularly in the East Java region. One approach to enhance the utility and economic significance of these flowers involves isolating their active component, specifically anthocyanin. Anthocyanins have several health benefits, especially in preventing cardiovascular disease, improving vision, and being anti-diabetic, anti-inflammatory, and anti-cancer. The isolation methods used in this research were conventional solvent extraction (CSE) and ultrasonic-assisted extraction (UEA) methods. The use of UAE has been experimentally proven to accelerate the extraction rate of bioactive compounds. This dal is caused by a driving force in the form of energy produced from bubble cavitation resulting from ultrasonic energy. The specific aim of this study was to compare the effectiveness of the two methods in anthocyanin isolation. The extraction stages were carried out at 30, 40, 50, 60, and 70°C operating temperatures, with an S/L ratio of 1:10, 1:15, 1:20:1:25, and 1:30 with samples conditioned in dry and wet conditions. The optimal conditions for ultrasound-assisted extraction (UEA) involve dry samples with a S/L ratio of 1:30 at a temperature of 70°C with the resulting final concentration of 16.5234 g/L. This configuration ensures an efficient extraction process, completed in less than 30 minutes, thereby preventing the degradation of anthocyanins. Analysis indicates that the extraction process adheres to a second-order kinetic model with a constant (k) of 0.1039. Stability testing revealed that the first–order kinetic model accurately represents the impact of temperature on anthocyanin degradation.